Knowing about Genocide Armenian Suffering and Epistemic Struggles - Savelsberg, Joachim J. (University of California Press, 2021)
How do victim and perpetrator peoples generate conflicting knowledge about genocide? Using a sociology of knowledge approach, Joachim J. Savelsberg answers this question in the context of the Armenian genocide committed during the First World War. Focusing on Armenians and Turks, Savelsberg examines strategies of silencing, denial, and acknowledgment in everyday interactions, public rituals, law, and politics. He draws on interviews, ethnographic accounts, documents, and eyewitness testimony to illuminate the social processes that drive dueling versions of history. Ultimately, this study reveals the counterproductive consequences of denial in an age of human rights hegemony, demonstrating the implications for populist disinformation campaigns against overwhelming evidence. "This pioneering book is critical for understanding the background to Turkish denial as the final stage of genocide. Savelsberg's epistemic study is a warning against a revived shade of an Orwellian order, with its 'alternative realities' and 'post-truths.'" CLAIRE MOURADIAN, Centre National de la Recherche Scientifique, Paris "Knowledge denial is a deadly phenomenon and an urgent problem. Through painstaking research, unrivaled expertise, and ethical commitment, Joachim J. Savelsberg illuminates how mass harm has been negated or acknowledged." LOIS PRESSER, author of Inside Story: How Narratives Drive Mass Harm "Savelsberg has done a brilliant job in this unique work that for the first time analyzes the Armenian genocide from the vantage point of knowledge construction. A must-read for all interested in collective violence, social movements, and sociology of knowledge." FATMA MÜGE GÖÇEK, author of Denial of Violence: Ottoman Past, Turkish Present, and Collective Violence against the Armenians, 1789-2009